Interpretation of onomapoetic vocabulary in the postmodernist drama of M. Yu. Ugarov «Doves» - Petrachkova, Inna M. (Journal of the Belarusian State University. Philology, 2023)
The article examines proper names, functioning in the artistic context of the play «Doves» by M. Yu. Ugarov. All onomapoetic means are considered, represented by individual authorial and precedent anthropoetonyms, nominating the plot and extra-plot characters of the nostalgic drama, variants of personal names, as well as propria units of the second plan, the so-called background poetonyms. The onomapoetic space of the play is analysed. The types of anthropoetonyms, their linguistic and extralinguistic possibilities are revealed. The conditionality of the choice of onomapoetic means by the individual authors context, reﬂecting the views of the modern Russian playwright on historical events, has been established. The informational potential of onomapoetic vocabulary is demonstrated, which is most fully revealed in the course of the analysis of the interaction between the artistic context and poetonyms of the drama. The correlation of the interpretation of the characters name with the chronotope of the events described in the play, the artistic context and the embodiment of the authors position is shown. The hidden meanings of the nominations are revealed, due to the fragments of the play and the concept of the playwright. Onomapoetic tendencies of creating literary names and using their capabilities, which are inherent in the idiostyle of M. Yu. Ugarov (combination of classical innovative features), are determined.